EMBOLIC MYOCARDIAL INFARCTION. EXPERIENCE IN DIAGNOSIS AND MANAGEMENT - A. S. Shilova; E. M. Gilyarova; D. A. Andreev; D. Yu. Shchekochikhin; N. A. Novikova; M. Yu. Gilyarov (Рациональная фармакотерапия в кардиологии)
Acute myocardial infarction (AMI) is one of the main causes of morbidity and mortality, both in the Russian Federation and around the world. Approximately, in up to 10% of patients with clinical diagnostic features of AMI, early angiography does not reveal an occluded vessel or possibly any evidence of coronary artery disease. These patients constitute an intriguing subgroup referred to as “Myocardial Infarction with Non-Obstructive Coronary Arteries” (MINOCA). MINOCA is a collective concept that unites many different pathologies, which determines the essential heterogeneity of the etiological factors. Coronary artery embolism is recognized as an important non-atherosclerotic cause of AMI. In turn, the most common underlying disease in those with coronary embolism is the atrial fibrillation. The advantages of reperfusion strategy and cardioprotective therapy in the treatment of obstructive arteriosclerosis are well studied, widely presented in the literature and supported by a strong evidence base, while the issues of diagnosis and treatment of patients with MINOCA are currently widely discussed We present two clinical cases of embolic myocardial infarction in patients with atrial fibrillation, diagnosed in our clinic in 2017.